2011
DOI: 10.1039/c1mt00031d
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium study on the interaction of phytic acid with polyamines and metal ions

Abstract: Interaction of phytic acid (myo-inositolhexakisphosphoric acid, IP) and polyamines (A = en, tn, Put, dien, 2,3-tri, 3,3-tri, Spd, 3,3,3-tet, spermine(Spm)) have been studied by potentiometric and (31)P-NMR techniques. The non-covalent interactions have led to the formation of stable molecular complexes of (IP)H(n)(A) type at the 1:1 molar ratio of the ligands, but of different numbers of protons. The IP protonation constants, stability constants of the molecular complexes and metal (Mg(2+)) complexes have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
5
16
1
Order By: Relevance
“…35 For put, cad, spd and spm, various studies were previously carried out, even though none of them was performed under the same experimental conditions. 29,30,35,58 A similar behaviourthat is, a decrease in protonation constant values − is found for Me 2 hexaen, Me 2 heptaen and Me 2 octaen in 0.15 M Me 4 NCl at 37.0°C with respect to previous values obtained at 25.0°C in 0.15 M NaClO 4 solutions, 32 in agreement with the exothermicity of the protonation processes involving these polyamines. Almost all other previous protonation constants were measured at 20 or 25°C.…”
Section: And Polyaminessupporting
confidence: 83%
See 2 more Smart Citations
“…35 For put, cad, spd and spm, various studies were previously carried out, even though none of them was performed under the same experimental conditions. 29,30,35,58 A similar behaviourthat is, a decrease in protonation constant values − is found for Me 2 hexaen, Me 2 heptaen and Me 2 octaen in 0.15 M Me 4 NCl at 37.0°C with respect to previous values obtained at 25.0°C in 0.15 M NaClO 4 solutions, 32 in agreement with the exothermicity of the protonation processes involving these polyamines. Almost all other previous protonation constants were measured at 20 or 25°C.…”
Section: And Polyaminessupporting
confidence: 83%
“…It has been shown that, in similar complexes, protonation is governed by the different basicity of the interacting species. 30 Table 2). † For all the studied systems, the complexes detected have a 1 : 1 amine : InsP 6 molar ratio in different protonation states.…”
Section: Insp 6 Interaction With Polyamines: Potentiometric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LSF experiments, the TP concentration decreased by 23% when solution pH was increased from 4.5 to 8 (Figure ). Because P i concentration decreased by only 11% after pH adjustment, the observed removal was attributed to phytate precipitation with either Mg or K, which were both highly concentrated in LSF (Table ) (Nolan, Duffin, & McWeeny, ; Odani, Jastrzab, & Lomozik, ). Although phytate concentrations were not directly measured, it was assumed that, as the major P o species in LSF and TSF, most P o removal was associated with the corresponding phytate removal.…”
Section: Resultsmentioning
confidence: 99%
“…Phytic acid takes place in many physiological reactions, and its use in many fields is continuously growing, mainly thanks to its binding ability towards many metal and organo-metal cations, as well as other ligands [1][2][3][4][5][6]. These properties, together with many other possible use of phytate (e.g., in electrochemistry), are well described in many books and papers (e.g., [7][8][9][10][11][12][13][14][15][16][17][18] and references therein).…”
Section: Introductionmentioning
confidence: 96%